Connexin 50 gene on human chromosome 1q21 is associated with schizophrenia in matched case–control and family-based studies. Issue 8 (5th April 2007) - Ni, Xingqun; Valente, Jose; Azevedo, Maria H; Pato, Michelle T; Pato, Carlos N; Kennedy, James L
Abstract : Background: The gap junction subunit connexin permits direct intercellular exchange of ions and molecules including glutamate, and plays an important role in the central nervous system. The connexin 40 (Cx40) and connexin 50 (Cx50) genes are located on chromosome 1q21.1, a region strongly linked with schizophrenia. These lines of evidence suggest that Cx40 and Cx50 may play a role in schizophrenia. Methods: Using an allele-specific PCR assay, four polymorphisms each were genotyped for Cx40 and Cx50 in 190 Caucasian patients with schizophrenia and 190 controls matched for sex, age and ethnicity. Following up, Cx50 rs989192 and rs4950495 were investigated in 99 Canadian and 163 Portuguese trios and nuclear families with schizophrenia probands. Hardy–Weinberg equilibrium and linkage disequilibrium (LD) block identification was carried out with HaploView, and association analysis for alleles and haplotypes with a permutation test of 10 000 simulations was carried out using the UNPHASED software program. Results: Distributions of genotype frequencies of all markers were in Hardy–Weinberg equilibrium in Caucasian patients, controls and families. One rs989192-rs4950495 LD block was found in patients but not in controls. We found a significant association between the Cx50 rs989192-rs4950495 haplotype and schizophreniay (χ 2  = 29.55, p<0.01). The A-C haplotype had a higher frequency in patients (χ 2  = 7.153, p<0.01). Family studies also showed that the A-C haplotype was transmitted more often to patients with schizophrenia (χ 2  = 8.43, p<0.01). No association of Cx40 with schizophrenia was found for allele, genotype or haplotype analyses. Conclusions: Our matched case–control and family study indicate that Cx50, but not Cx40, may play a role in the genetic susceptibility to schizophrenia.